Nursing and "being with" in a world with COVID-19: an existentialist look - Carolina Giordani da Silva; Maria da Graça Oliveira Crossetti; Maravilla Giménez-Fernández (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective To reflect on nursing from an existentialist perspective, in which "being-with" has been shown to be the best type of care in a world with Covid-19. Method Reflective theoretical study on nursing in the context of a pandemic using an existentialist philosophical theoretical framework. Results Nursing is now perceived by society as a profession whose practices are beyond the clinical conditions that affect individuals who live with this pandemic, as taking care of others is not only performing technical actions, but means, fundamentally, taking sensitive ones, like "being-with" in a present and authentic way. Final considerations The pandemic has caused changes in the way human beings relate to the world, leading to reflections on values due to the restrictions imposed by it. In this scenario, nurses becomes visible, being the protagonists in the different care spaces, since the focus of its practice is existential care, which is established through relationships in encounters between beings, thus making "being-with" possible.